Oscillation and Asymptotic Behavior of Higher-Order Nonlinear Differential Equations - J. Džurina; B. Baculíková (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to offer a generalization of the Philos and Staikos lemma. As a possible application of the lemma in the oscillation theory, we study the asymptotic properties and oscillation of the nth order delay differential equations (E)(r(t)[x(n−1)(t)]γ)′+q(t)xγ(τ(t))=0. The results obtained utilize also the comparison theorems.